Macular edema secondary to malignant Hypertension managed with Intravitreal Bevacizumab - Dhami, Abhinav; Vichu, Latha; Sen, Parveen (Nepalese Journal of Ophthalmology, 2019)
Introduction: Intravitreal anti VEGF agents are used in a variety of retinal pathologies to decrease the VEGF levels resulting due to breakdown of the blood retinal barrier hence decrease the exudation from vessels which causes macular edema (ME). Case: A 61year old patient presented with sudden decrease in vision in both eyes with a history of systemic malignant hypertension leading to macular edema as documented on optical Coherence Tomography (OCT) in both eyes. The foveal thickness (FT)of 536 and 328 microns (μ) were observed in the right and left eye each. He was advised intravitreal anti vascular endothelial growth factor (VEGF) in both eyes and advised complete systemic evaluation with the physician. Following one month postintravitreal bevacizumab ( IVB) injection in right eye, marked visual improvement was noted with concomitant significant reduction in macular edema in both eyes. Observation: Single Bevacizumab injection with control of hypertension in our patient resulted in rapid resolution of the macular edema and early visual recovery. Intravitreal anti VEGF is an effective treatment option in eyes due to hypertensivemaculopathy especially to gain speedy visual recovery. Conclusion: The case gives a unique outlook to the course of ME in the single patient with malignant HTN with or without IVB injection. We believe that anti VEGF injections may result in rapid recovery in vision and minimize the risk of permanent vision loss in eyes with malignant hypertension.